Popular Schools of Jurisprudence and Reasons for its Popularity and Spread - Authentic Historical Study - - Khaled Dou (Social Empowerment Journal, 2021)
This research tackles the famous schools of jurisprudence and the reasons for their popularity and spread in an authentic historical study. Also, it aims to explain the spread history of the Islamic jurisprudence, and the extent of its relevance between the stages of Islamic legislation and provision sequencing. Besides, the paper attempts to determine the reasons for the spread of a school's thought or a specific orientation and its impact on the history of jurisprudence and methods of deriving provisions.One of the most important findings of the research is that schools of jurisprudence are numerous as they are generated from the ideas established by a certain imam and disagree with the ideas of others in proposing and inferring. Yet, most of them became obscure and remained only among the folds and lines of books and manuscripts. Besides, some schools of jurisprudence became famous due to the interests of researchers and students in them.